ENT 600 : Prosignal Engineering Sdn. Bhd. / Mohammad Amirulhaikal Mohamed Razali - Mohamed Razali, Mohammad Amirulhaikal; Muhamad Sharifuddin, Muhammad Aliff; Habbibollah, Muhammad Haziq; Eliasa', Muhammad Syazwan; Husin, Haziq (2019)
As part of the requirement in this subject, ENT 600 we are required to propose with a case study relating to engineering. Our case study is interview the company which is Prosignal Engineering Sdn. Bhd. which is located at Subang, Selangor, Malaysia, is known as one of the large maintenances and services company in this country. The company are able to design, supply, install, integrate and maintain the most effective and appropriate system and equipment to suit a particular environment at the most economical cost without compromising on quality. During interview, we were tasked to checking the company background to more detail. This interview identify several problems that this company have such as financial management issues and also limit the workers. Therefore, to overcome this issue we are suggests several solution to overcome this problems.